Idiopathic (benign) intracranial hypertension-induced sudden hearing loss: A rare case: Idiopathic intracranial hypertension-induced sudden hearing loss - Akpınar, Meltem; Karatepe, Elifnur (Journal of Surgery and Medicine, 2025)
Sudden hearing loss (SHL) is a clinical condition characterized by the acute onset of sensorineural hearing loss. Although many etiological factors have been reported, it is primarily idiopathic. Idiopathic Intracranial Hypertension (IIH) is a syndrome that presents signs of increased intracranial pressure in the absence of any intracranial lesion, meningeal inflammation, or venous obstruction. In our case, a patient diagnosed with SHL presented with hearing loss and visual field constriction. An investigation into etiological factors identified IIH. Although rare, IIH can cause SHL. It is crucial to consider this possibility during the diagnostic process and carefully plan the treatment based on the potential etiology.